Государственное регулирование и поддержка предпринимательства. (Путеводитель предпринимателя, 2020)
Business associations are able to solve major economic and social challenges, as well as support the economy and in time the organization to adapt to new market conditions. Since the state influence is decisive in creating the conditions for the formation and development of all economic actors, the problems of government regulation and business support is now particularly relevant. We defined the place of entrepreneurship in the economic life of the country, analyzed the state of small and medium businesses in Russia, highlighted their main concerns and expectations identified the need for support, as well as the basic directions of state support and regulation of business activity.